CVS0 224: A TRANSITIONAL DISK IN THE 10 MYR 25 ORI AGGREGATE - N. Calvet (Revista Mexicana de Astronomía y Astrofísica, 2009)
We present optical and infrared observations of CVSO 224, the sole transitional disk located within the -10 Myr year old 25 Orionis group of Orion OB1a. The Spitzer IRS spectrum reveals an optically thick disk truncated at - 7 AU, with an inner region lled with optically thin dust, reminiscent of the structure of the only other -10 Myr year old transitional disk studied in detail, namely, TW Hya. As in TW Hya, the grains in this region have grown to ym sizes, signicantly larger than in the inner regions of the transitional disks in Taurus. The H prole in our high resolution HECTOCHELLE spectrum of CVSO 224 reveals broad wings, indicative of magnetospheric accretion, despite the previous classication of WTTS for this object. The derived mass accretion rate is about 10 times lower than in TW Hya, but consistent with expected decay of mass accretion rate with age.